Manajemen Rantai Pasok Agroindustri Pala di Desa Morella Kecematan Leihitu Kabupaten Maluku Tengah - Manurung, Anjelina; Timisela, Natelda R; Tuhumury, Maisie T F (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to analyze the mechanism of supply chain flow, the value of supply chain performance, and supply chain efficiency in the Morella nutmeg juice MSME group. This research was conducted for 1 month in the nutmeg agro-industry in Morella Village, Leihitu District, Central Maluku Regency. The research method used was purposive sampling to determine the sample based on the characteristics or mechanism characteristics of the nutmeg juice supply chain. This study was analyzed using a descriptive method to describe the mechanism of the nutmeg juice agro-industry supply chain. The results showed that supply chain members of the Nutmeg Juice MSME Group consisted of suppliers, manufacturers, distributors, and consumers. There are two types of supply chain models for the Pala Morella Juice MSME group. The first is between manufacturers and distributors who work together to market nutmeg juice products to consumers. The second supply chain flow is the relationship between manufacturers, which is direct to the consumer, meaning that consumers come directly to the product production site and buy products directly from the company. Information flow occurs in two directions, for financial flows running from consumers-distributors-manufacturing-suppliers. Product flow starts from manufacturer-distributor-consumer. The flow of raw materials occurs only in one direction, namely from the nutmeg farmers in Morella Village.